A Novel Tool to Mitigate By-Catch Mortality of Baltic Seals in Coastal Fyke Net Fishery - Oksanen, Sari M.; Ahola, Markus P.; Oikarinen, Jyrki; Kunnasranta, Mervi (Plos, 2015)
Developing methods to reduce the incidental catch of non-target species is important, as by-catch mortality poses threats especially to large aquatic predators. We examined the effectiveness of a novel device, a "seal sock", in mitigating the by-catch mortality of seals in coastal fyke net fisheries in the Baltic Sea. The seal sock developed and tested in this study was a cylindrical net attached to the fyke net, allowing the seals access to the surface to breathe while trapped inside fishing gear. The number of dead and live seals caught in fyke nets without a seal sock (years 2008-2010) and with a sock (years 2011-2013) was recorded. The seals caught in fyke nets were mainly juveniles. Of ringed seals (Phoca hispida botnica) both sexes were equally represented, while of grey seals (Halichoerus grypus) the ratio was biased (71%) towards males. All the by-caught seals were dead in the fyke nets without a seal sock, whereas 70% of ringed seals and 11% of grey seals survived when the seal sock was used. The seal sock proved to be effective in reducing the by-catch mortality of ringed seals, but did not perform as well with grey seals.